Clinical Profile, Pharmacological Treatment, and Predictors of Death Among Hospitalized COVID-19 Patients With Acute Kidney Injury: A Population-Based Registry Analysis - Gutiérrez-Abejón, Eduardo; Martín-García, Débora; Tamayo, Eduardo; Álvarez, F. Javier; Herrera-Gómez, Francisco (Frontiers in Medicine, 2021)
Introduction: One of the most pejorative clinical outcomes of coronavirus disease 2019 (COVID-19) pandemic was acute kidney injury (AKI). Methods: This manuscript presents results from a population-based registry study assessing treatment, comorbidities and predictors of hospital death among COVID-19 patients with AKI from March 1st to May 31th, 2020. Death, oxygen delivery and ventilation, acute dialysis need, medicines use, and various clinical outcomes, in addition to hospital and intensive care unit (ICU) length of stays, were evaluated. Results: In Castile and Leon, the largest region of Spain, 10.87% of the patients admitted for COVID-19 (n=7,307) developed AKI. These patients were known by having hypertension (57.93%), cardiovascular disease (48.99%), diabetes (26.7%) and chronic kidney disease (14.36%), and they used antibiotics (90.43%), antimalarials (60.45%), steroids (48.61%), antivirals (33.38%), anti-systemic inflammatory response syndrome (SIRS) drugs (9.45%), and tocilizumab (8.31%). Mortality among patients with AKI doubled that observed in patients without AKI (46.1% vs. 21.79%). Predictors of hospital death in COVID-19 patients with AKI were: ventilation needs (OR=5.9), treatment with steroids (OR=1.7) or anti-SIRS (OR=2.4), severe acute respiratory syndrome (SARS) occurrence (OR=2.8), and SIRS occurrence (OR=2.5). Conclusions: AKI is frequent and a serious complication among COVID-19 patients, with a very high mortality, that requires more attention by treating physicians, when prescribing medicines and by looking to the occurrence of manifestations proper of the disease such as SARS or SIRS.